Control strategy for single-phase PWM rectifiers - Kukrer, O; Komurcugil, H (Iee-Inst Elec Eng, 1997)
A new control strategy is proposed for single-phase pulsewidth modulation (PWM) rectifiers of the voltage-source type. The method eliminates the need for sensing the AC-side current. Analysis of the method and computer simulation results for steady-state operation are presented.
Keywords: PWM power converters